Meningeal chondroma in a young female - Kumari Niraj; Sahu Rabi; Krishnani Narendra (Wolters Kluwer Medknow Publications, 2010)
Meningeal chondroma is a rare intracranial neoplasm. It is usually diagnosed clinically as meningioma. Histologically it may have a differential diagnosis of chordoid meningioma, a malignant lesion, and needs radiotherapy. A chondroma is a benign lesion where surgical removal is the treatment. A 20-year-old female presented with symptoms of space occupying lesion which was clinically and radiologically considered meningioma. On histopathology, the lesion turned out to be a chondroma. Meningeal chondroma is a benign lesion for which surgical removal is the curative treatment. No further treatment in the form of radiation is required.